Ibn Asakir and early Islamic history - Lindsay, James E., 1957- (SLAEI - Studies in Late Antiquity and Early Islam Ser., 2021)
Ibn ʻAsākir's massive Taʼrīkh madīnat Dimashq (TMD) is a veritable gold mine of information for our understanding of the first five and one-half centuries of Islamic history. This book offers important insights on the mechanics of Arabic historiography, in particular on biographical sources from the Middle period. Moreover, two contributions show that Ibn ʻAsākir pursued a political and sectarian agenda within his TMD. 1. James E. Lindsay, Ibn ʻAsākir, His Taʼrīkh madīnat Dimashq and its Usefulness for Understanding Early Islamic History; 2. Suleiman A. Mourad, Jesus According to Ibn ʻAsākir;